Wobec zmian – czytanie w nowym kontekście kulturowym - Stano-Strzałkowska, Sylwia (Kultura-Społeczeństwo-Edukacja, 2019)
The aim of the article is to present modern readership habits and the impact of new technologies development on them. Those technologies and social changes can also pose a danger or provide support for the development of readership; however, the point is how to skilfully make use of them. Readership plays a significant role in modern societies. It is considered not only a socio-cultural tool giving people equal chances in life and facilitating dialogue between different cultures, but also an important economic development factor. Nevertheless, the level of readership keeps successively decreasing in developed countries. Poland is not an exception – on the contrary, the level of readership is decreasing faster than in other developed countries. This article is an outline of opportunities and barriers as well of new technologies affecting readership. The relations between those opportunities or barriers and the level of readership are also discussed. The article includes a range of examples of positive solutions from abroad, suitable for introduction in Poland.